Foreign language learning and the mismatch negativity (MMN): A longitudinal ERP study - Andreas Højlund; Nynne Thorup Horn; Stine Derdau Sørensen; William B. McGregor; Mikkel Wallentin (Neuroimage: Reports, 2022)
An early component of the auditory event-related potential (ERP), the mismatch negativity (MMN), has been shown to be sensitive to native phonemic sound contrasts. The potential changes to this neural sensitivity from foreign language learning have only been marginally studied. The existing research seems to suggest that the neural sensitivity as indexed by the MMN can adapt to foreign language sound contrasts with very target-specific training, but whether the effects are long-lasting or generalize to proper foreign language learning is yet to be investigated in a viable longitudinal study design. We therefore recorded electroencephalography (EEG) from two groups of language officer cadets (learning either Arabic (n = 8) or Dari (n = 12)) while they listened to speech sound contrasts from both languages. We recorded their EEG four times over the course of 19 months of intensive foreign language training (immediately before they started, after three weeks, after six months, and after 19 months).We did not find any language-specific effects of learning on the cadets’ MMNs to the speech sound contrasts. We did, however, elicit statistically reliable MMNs to both sound contrasts for both groups at most of the four times of measurement. Furthermore, we found that the Arabic learners’ MMNs to the Arabic stimuli diminished over time, and that the Dari learners’ P3a responses to the Arabic stimuli diminished over time. Correlating the participants’ MMNs with their behavioral responses to the language stimuli did not reveal any strong links between behavior and neurophysiology. However, those Dari learners whose MMNs to the Dari stimuli increased the most within the first three weeks, also received the highest grades on a listening task after 17 weeks.